Censorship: Instagram (Turkey) - Voidly (2024)
CRITICAL severity censorship detected in Turkey. Confidence: 75%. Data sourced from CensoredPlanet.
Censorship Incident ID: TR-2024-0002
Keywords: censorship; TR; censorship; critical